Ecological monitoring and evidence‐based decision‐making in America's National Parks: highlights of the Special Feature - Thomas J. Rodhouse; Christopher J. Sergeant; E. William Schweiger (Ecosphere, 2016)
Abstract In this Special Feature, we celebrate 100 years of National Park Service science by highlighting contributions from the agency's Inventory and Monitoring Division. This broad body of work coalesces into several themes, including the role of protected areas in understanding rapid global change and the growing interest in place‐based ecological insights that contextualize scientific information from protected areas across broader scales. Finally, we illustrate progress on the long‐sought integration of science into the resource management strategies implemented within “America's Best Idea,” now more important than ever given the many challenges our nation's parks face.